Digestibility of microbial and mussel meal for Arctic charr (Salvelinus alpinus) and Eurasian perch (Perca fluviatilis) - Langeland, M.; Vidakovic, A.; Vielma, J.; Lindberg, J. E.; Kiessling, A.; Lundh, T.
2016